2014
DOI: 10.1002/dvg.22780
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest cell‐specific inactivation of Nipbl or Mau2 during mouse development results in a late onset of craniofacial defects

Abstract: Nipbl (Scc2) and Mau2 (Scc4) encode evolutionary conserved proteins that play a vital role for loading the cohesin complex onto chromosomes, thereby ensuring accurate chromosome segregation during cell division. While mutations in human NIPBL are known to cause the developmental disorder Cornelia de Lange syndrome, the functions of Nipbl and Mau2 in mammalian development are poorly defined. Here we generated conditional alleles for both genes in mice and show that neural crest cell-specific inactivation of Nip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
(26 reference statements)
3
19
0
Order By: Relevance
“…On this hybrid background, wildtype and Bmp4 +/− mice (N = 8) have 13 pairs of ribs, but both Nipbl +/− and Nipbl +/− ; Bmp4 +/− mice display 14 pairs of ribs at a frequency greater than 90%. We noted that in 8 of 11 mice with supernumerary ribs, these ribs had a stunted appearance; stunted extra thoracic ribs were also noted by Smith et al [] in their study of a different line of Nipbl +/− mice, and are, importantly, a common finding in CdLS [Braddock et al, ; Bhuiyan et al, ]. Interestingly, supernumerary ribs were never seen when mice were maintained on a CD1 background, in which 14 ribs is the normal wildtype number.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…On this hybrid background, wildtype and Bmp4 +/− mice (N = 8) have 13 pairs of ribs, but both Nipbl +/− and Nipbl +/− ; Bmp4 +/− mice display 14 pairs of ribs at a frequency greater than 90%. We noted that in 8 of 11 mice with supernumerary ribs, these ribs had a stunted appearance; stunted extra thoracic ribs were also noted by Smith et al [] in their study of a different line of Nipbl +/− mice, and are, importantly, a common finding in CdLS [Braddock et al, ; Bhuiyan et al, ]. Interestingly, supernumerary ribs were never seen when mice were maintained on a CD1 background, in which 14 ribs is the normal wildtype number.…”
Section: Resultssupporting
confidence: 73%
“…None of these phenotypes was observed in wildtype mice or mice that were Nipbl +/− or Bmp4 +/− alone. Interestingly, we did not observe the misalignment of ossification centers in the sternum that Smith et al [] noted in a different strain of Nipbl +/− mice, although we did observe a further decrease in ossification of sternabrae in Nipbl +/− ; Bmp4 +/− embryos, compared to Nipbl +/− mice (not shown).…”
Section: Resultssupporting
confidence: 46%
“…4) in expression at basal level and upon RA treatment, that can be explained as if cells derived from NIPBL mutated patients are not capable of responding to RA signaling as efficiently as in healthy controls. This new information is very important, also in light of recent findings that show how cohesinopathies are linked to NCC impairment (Smith et al, 2014;Schuster et al, 2015). Indeed, mammalian NCC are specified by WNT signaling (Lee et al, 2004;Rabad an et al, 2016), and NCC migration is controlled by RA morphogenic activity (Maschhoff and Baldwin, 2000).…”
Section: Discussionmentioning
confidence: 84%
“…The second possibility is that Scc4 is not essential in humans. Studies have shown that RNA knockdown of SCC4 in HeLa cells causes a chromosome segregation defect, and that knockout SCC4 mice showed a more severe phenotype than did SCC2 knockout mice ( Seitan et al 2006 ; Smith et al 2014 ). Third, inactivation of Scc4 by a mutation is lethal.…”
Section: Discussionmentioning
confidence: 99%
“…Scc2 promotes gene expression, and mutations in the gene were identified as the main cause for the developmental disorder Cornelia de Lange syndrome (CdLS) ( Krantz et al 2004 ). Human SCC4 is involved in neural development ( Smith et al 2014 ). Despite the unquestioned importance of the loader in cohesin activity, cell functionality and human health, very little is known about the molecular mechanism involved.…”
mentioning
confidence: 99%